ELECTROCHEMICAL DECOLORIZATION OF DIRECT BLACK TEXTILE DYE WASTEWATER (Journal of Engineering, 2011)
Electrochemical decolorization of direct black textile dye was studied in the presence of sodiumhydroxide (NaCl). Electrochemical cell occupy about 1 liter of working electrolyte supplied with graphiteelectrodes for both anode and cathode was constructed for this purpose. Decolorization percent, treatment time, power consumption, and pH were studied as a function of the applied voltage and salt concentration. Results show that decolorization increase with increasing salt concentration and applied voltage. Best decolorization of 86% can be achieved after 17 min at 7 volt and 5 g/l salt concentration. Further decolorization can be achieved but this will be accompanied with a sharp increase in power consumption. No significant decrease in pH value was observed at the end of each experiment.